PERAN GURU PENDIDIKAN AGAMA KRISTEN DALAM MEMBENTUK KARAKTER SISWA DI ERA INDUSTRI 4.0 - Augusni Hanna Niwati Telaumbanua (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2020)
Abstract: In this paper the authors reveal the role of Christian Religious Education in shaping the character of students in the era of the industrial revolution 4.0, becoming a new "world" for human life that has a broad impact on the structure of human life, including Christian education. By looking back at the role of Christian Religious Education, this paper emphasizes that Christian Religious Education is a forum for the formation and nurturing of student character so that one day they can become individuals with Christian character who can voice God's truth amid various problems faced. Besides, this also shows part of the role of Christian Religious Education in supporting the transformation of the character of the nation's children. Teachers have a major role in education which influences through teaching and modeling. The teacher's responsibility is to help students develop their potential to the fullest. The potential of students that must be developed does not only concern intelligence and skills but also all aspects of personality. Teachers are not only required to have an understanding or ability in the field of learning and learning but also in motivating students. Christian Religious Education Teachers (PAK) play a role in teaching spiritual values and motivating their students. PAK teachers must understand the concepts of motivation so that they can function as facilitators for the development of students, both in terms of intellectual, emotional, social, and mental-spiritual aspects.Keywords : Role, Student Character, Industrial Era 4.0